Integrasi Keilmuan Program Studi Tadris (Umum) Fakultas Tarbiyah dan Keguruan IAIN Raden Intan Lampung - Murtadho, Ali (Universitas Islam Negeri Raden Intan Lampung, 2016)
Science (science) and religion (religion) in practice often have a different paradigm. Science (Science) in seeking and finding the truth generally dotted beneath the rationalism-empiricism. Science paradigm is generally considered to have a neutral nature of ethics and ideology-neutral, so it is objective. While the paradigm used religion (religion) in seeking and finding the truth is usually based on dogma, rites, and myths. In the spirit of transcendental religion (divine revelation) which is absolute. Therefore, the truth of religion can not be denied. This is what makes the two camps often do not greet each other, eventually gave birth to the attitude of negating one another. Reality is indeed pointed out, the existing education system in Indonesia there are two kinds: general education and education (to) religion (an). In practice both the education system, as being in